Urban Heritage Planning in Tehran and Beyond Sequences of Disrupted Spatial-Discursive Assemblages - Yadollahi, Solmaz (Cultural Heritage Studies, 2023)
Despite the impact of ideological rigidity, the primary challenge of heritage planning in Tehran and beyond lies not in the dominance of an inflexible Authorized Heritage Discourse, but rather in the absence of stable spatial-discursive and administrative structures. Solmaz Yadollahi maps the historical trajectory of conservation and urban heritage planning in Iran, depicting a discursive-spatial assemblage that tends to knock down its accumulated resources. This is in line with Katouzian's portrayal of Iran as a pick-axe society. Residing within this society, the studied assemblage strives to deconstruct the prevailing structures and usher in a fresh one, paradoxically perpetuating the very cycle it seeks to escape.